Slides to Philosophy 167: Class 1 -- Overview of the Course;Ptolemaic Astronomy -- Part 9. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 1, Part 9.